2020
DOI: 10.1007/s10346-020-01524-1
|View full text |Cite
|
Sign up to set email alerts
|

Remote thermal detection of exfoliation sheet deformation

Abstract: A growing body of research indicates that rock slope failures, particularly from exfoliating cliffs, are promoted by rock deformations induced by daily temperature cycles. Although previous research has described how these deformations occur, full three-dimensional monitoring of both the deformations and the associated temperature changes has not yet been performed. Here we use integrated terrestrial laser scanning (TLS) and infrared thermography (IRT) techniques to monitor daily deformations of two granitic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Both techniques are suited to site scale investigation and yield DEMs which can be used to estimate surface changes and generate modelling volumes in ERI. Terrestrial (or ground based) LIDAR is a well-established tool for monitoring rock falls and natural slope movements, be it through permanent monitoring solutions (Lingua et al 2008) or repeated surveys (Delacourt et al 2007;Guerin et al 2021;Palenzuela et al 2016;Rosser et al 2007). Recent advances in structure from motion (SfM) photogrammetry have yielded centimetric resolutions such that they are comparable to terrestrial LiDAR scans and both are suited to the purposes of ERI.…”
Section: Recording Geomorphological Changesmentioning
confidence: 99%
“…Both techniques are suited to site scale investigation and yield DEMs which can be used to estimate surface changes and generate modelling volumes in ERI. Terrestrial (or ground based) LIDAR is a well-established tool for monitoring rock falls and natural slope movements, be it through permanent monitoring solutions (Lingua et al 2008) or repeated surveys (Delacourt et al 2007;Guerin et al 2021;Palenzuela et al 2016;Rosser et al 2007). Recent advances in structure from motion (SfM) photogrammetry have yielded centimetric resolutions such that they are comparable to terrestrial LiDAR scans and both are suited to the purposes of ERI.…”
Section: Recording Geomorphological Changesmentioning
confidence: 99%
“…Daily temperature changes affected the upper 0.21 to 0.42 m assuming a 12 h temperature cycle and a thermal diffusivity of between 1 and 2 mm s −2 typical for metamorphic rocks (Cermák and Rybach, 1982;Vosteen and Schellschmidt, 2003). These rock depths correspond to daily temperature cycles in rockwalls observed in previous studies (Anderson, 1998;Gunzburger and Merrien-Soukatchoff, 2011). On an annual scale, thermal changes affected 4 to 8 m, and, therefore, the entire instru- 4).…”
Section: Cyclic Thermal Rock Deformationmentioning
confidence: 66%
“…Current research highlights the role of mechanical weathering (Eppes and Keanini, 2017). Diurnal and seasonal ambient meteorological changes causing cyclic heating and cooling (Gunzburger and Merrien-Soukatchoff, 2011;Collins and Stock, 2016), wet-dry cycles (Zhang et al, 2015), freeze-thaw cycles (Matsuoka, 2001(Matsuoka, , 2008 or active-layer thaw (Draebing et al, 2014(Draebing et al, , 2017a) produce critical and subcritical stresses that propagate micro-fractures (Eppes et al, 2018;Draebing and Krautblatter, 2019). Several studies investigated the influence of thermal changes on rockwalls and demonstrated that sudden erosion by thermal shock (Collins et al, 2018(Collins et al, , 2019 and slow thermally induced propagation of fractures in alpine rockwalls (Hasler et al, 2012;Collins and Stock, 2016;Weber et al, 2017) continuously weakens rock and can trigger rockfall (Ishikawa et al, 2004;Collins and Stock, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in thermally-induced effects on jointed rock masses [17,[35][36][37][38][39][40][41] requires an improvement in the techniques for temperature field analysis to integrate traditional direct contact methods [14,42]. In this sense, IRT surveys support the quantitative study of surface temperature fields over rock slopes, deriving distributed maps at their external interface.…”
Section: Discussionmentioning
confidence: 99%